Pemasaran Media Sosial Pada Pedagang Ayam Bakar Pak Aji Di Kawasan Medang, Gading Serpong - Santi Rimadias; Andreas Clarence (CV. ITTC INDONESIA, 2024)
UMKM play an important role in the country's economic development. Good marketing is needed for every UMKM player so they can sell their products and get good results. However, in reality, some UMKMs do not market their products on social media due to several factors that influence this. Rumah Makan Ayam Bakar Pak Aji has several problems or issues, starting from inactivity on Social Media & recognition of the restaurant's location via Google Maps. Social media marketing basically has high potential in reaching consumers more widely. UMKM Rumah Makan Ayam Bakar Pak Aji in terms of taste has met the expectations of society in general, it would be even better if marketing was also improved in the areas of social media and location recognition. Therefore, the community service team provided a solution to UMKM Ayam Bakar Pak Aji, by creating active social media to provide an introduction to Rumah Makan Ayam Bakar Pak Aji to the local community, as well as registering the restaurant's location on Google Maps with the aim of reaching the consumer market.